On Empowerment: Case of Women Fishermen in Sidoarjo using Social Entrepreneurship Approach - D. Tranggono; J. Dwiridhotjahjono; S. Andarini; R. Rasyidah (Nusantara Science and Technology Proceedings)
One of the social stratifications in the community who fall into the category below poverty is women fishermen. The complex factors that are interconnected are the main sources that weaken the ability of the community in building the region and improve its welfare and therefore causes poverty and alienation. In coastal areas, especially the group of women fishermen, poverty and alienation are special issues, a consistent issue showing almost in all area of Indonesian coastal. This article tries to invent a model of empowerment of local fishermen-based women in Sidoarjo Regency using social entrepreneurship approach. The model is then combined with a participatory approach which is defined as an effort to develop the independence and prosperity of fishermen women by increasing knowledge, attitude, skill, behavior, ability, awareness, and resource utilization and the optimization of local potential through the establishment of policies, programs, activities and assistance in accordance with the essence of the problems and priorities of fulfilling basic needs through the development of local economic potential by taking into account the sustainability of the environment in an integrated manner.